Burnout and Personality Profiles Among Chinese Nurses - Sijun Zhang; Ke Xiao; Zhen Tian (Behavioral Sciences)
Although many studies have examined the relationship between the five dimensions of personality and nurse burnout, few studies have examined the relationship between nurse burnout and the overall personality profile. In addition, nurses’ demographic characteristics have been found to be related to nurses’ burnout level, but the results have been inconsistent. This study aimed to determine personality profiles based on the Big Five personality model in a sample of Chinese nurses then analyze the relationship between burnout and personality profiles and demographics. A total of 1423 nurses were sampled and assessed using the Big Five Inventory and the Oldenburg Burnout Inventory. A k-means cluster analysis was used to divide participants into different personality profiles. Multivariate analysis of variance and binomial logistic regression were used to examine the relationship of burnout with personality profiles and demographics. Cluster analysis identified three personality profiles among nurses: resilient, ordinary, and distressed. For each dimension of the Big Five Inventory and Oldenburg Burnout Inventory, there was a significant difference between different personality profiles, with effect sizes being from 0.37 to 0.57. Nurses with a distressed personality profile were 4.52 times more likely to be diagnosed with burnout than nurses with an ordinary profile, while nurses with a resilient personality profile had a 55% reduction in burnout compared to nurses with an ordinary profile. The results suggested that hospital administrators should focus on nurses with a distressed personality profile to identify potential burnout nurses as early as possible. The findings also enabled hospital administrators to consider the different personality profiles of nurses and the specific requirements of the job to select suitable candidates.